Medical waste harmful to the environment and its civil liability (Albayan Scientific Journal, 2023)
This paper presents the reality of medical waste management in private health care centers of all kinds, including separating, transporting, managing and final disposal of medical waste, and the resulting health and environmental risks that directly affect the development process. As all forms of medical waste disposal pose a clear danger to all its employees and the rest of society, and this paper summarizes determining the responsibility for the damages resulting from medical waste, as the cause of the damage resulting from throwing this waste is responsible for the direction of the injured, criminal responsibility aimed at punishing the offender and civil liability Its purpose is to redress the damage done to the victim. Therefore, this research will talk about the elements of the legally protected environment from the effects of medical waste as a first topic that is divided into two demands, the first in which we know medical waste and its damages, and the second we show how to manage and handle medical waste In addition to a second topic in which we talk about the nature of civil liability for the environmental damages of medical waste. This topic is divided into two demands: the first, in which we explain the contractual responsibility for the environmental damages of medical waste, and the second, in which we clarify the tort responsibility for the environmental damages arising from medical waste.